One step forward to a scalable synthesis of platinum–yttrium alloy nanoparticles on mesoporous carbon for the oxygen reduction reaction. Issue 31 (21st July 2016) - Brandiele, R.; Durante, C.; Grądzka, E.; Rizzi, G. A.; Zheng, J.; Badocco, D.; Centomo, P.; Pastore, P.; Granozzi, G.; Gennaro, A.
Abstract : In this paper, we report the synthesis and characterization of nanoparticles of a Pt x Y alloy supported on a commercial mesoporous carbon with high mass and specific activity. Abstract : In this paper, we report the synthesis and characterization of nanoparticles (NPs) of a Pt x Y alloy supported on a commercial mesoporous carbon (MC). The NPs were prepared following a solid state synthesis in a quartz tubular furnace under H2 flow. The influence of Pt precursors on the NP shape and alloy formation was investigated together with the temperature and reaction time. The best synthesis afforded the obtainment of small spherical Pt x Y NPs (4 nm diameter) on the surface and inside pores of a MC with a maximum of alloy content of 41% with respect to the whole Pt loading. The electrochemical properties of Pt x Y NPs were investigated with special attention to their catalytic properties. The results in ORR studies showed that the catalyst containing the highest amount of Pt x Y alloy exhibits higher catalytic activity expressed in terms of mass and specific activity and comparable stability, after accelerated degradation tests, for oxygen reduction as compared to a standard Pt/C catalyst.